2018
DOI: 10.3390/su10051612
|View full text |Cite
|
Sign up to set email alerts
|

Policies and Predictions for a Low-Carbon Transition by 2050 in Passenger Vehicles in East Asia: Based on an Analysis Using the E3ME-FTT Model

Abstract: In this paper we apply a model of technological diffusion, Future Technology Transformations in the Transport Sector (FTT: Transport), linked to the E3ME macroeconomic model, to study possible future technological transitions in personal passenger transport in four East Asian countries. We assess how targeted policies could impact on these transitions by defining four scenarios based on policies that aim to reduce emissions from transport. For each country we find that an integrated approach of tax incentives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The study on the impact of emerging next-generation vehicles with smart vehicle technologies on the vehicle market [9] revealed that the cars using conventional motor fuels would keep their current position. The problem of the ecological danger of fuels and their combustion products requires one to look for integrated solutions, including new approaches in car and engine constructions [10]; improving the technological parameters of transport, with emphasis on multi-material construction for weight reduction [11]; increasing the adaptability of vehicles to operating conditions [12], in particular under weather changes [13], with application of such instruments as the dynamic vehicle scheduling [14]; tightening international and national requirements for fuel quality [15][16][17], use of tax instruments [3,[18][19][20][21]. Limited possibilities for improving the quality of motor fuels by refining methods [22][23][24] necessitate the use of fuel additives of various purposes, the combination of which in small amounts ensures the environmental and operational characteristics achieve the desired level [25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…The study on the impact of emerging next-generation vehicles with smart vehicle technologies on the vehicle market [9] revealed that the cars using conventional motor fuels would keep their current position. The problem of the ecological danger of fuels and their combustion products requires one to look for integrated solutions, including new approaches in car and engine constructions [10]; improving the technological parameters of transport, with emphasis on multi-material construction for weight reduction [11]; increasing the adaptability of vehicles to operating conditions [12], in particular under weather changes [13], with application of such instruments as the dynamic vehicle scheduling [14]; tightening international and national requirements for fuel quality [15][16][17], use of tax instruments [3,[18][19][20][21]. Limited possibilities for improving the quality of motor fuels by refining methods [22][23][24] necessitate the use of fuel additives of various purposes, the combination of which in small amounts ensures the environmental and operational characteristics achieve the desired level [25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…In terms of per capita emissions, the U.S.A. is the highest emitter, with 5.4 tonnes per capita, followed by Iran, the U.K., and the Russian Federation, with 1.7 tonnes per capita [15]. Many Asian countries have set long term targets to decarbonize transport [26,[55][56][57] and to keep global warming below 2 • C. However, transport CO 2 emissions grew by 41% in Asia during 2010-2019, with China and India registering the highest growth rates. Only Japan and the U.K. have managed to reduce transport emissions.…”
Section: Assessment Of Transport Sector Emissionsmentioning
confidence: 99%
“…Such transport decarbonization efforts need to start delivering results by 2030 and 2040. There are multiple mitigation options for reducing emissions from the transport sector, and several modeling approaches have been used to analyze transport decarbonization pathway scenarios [26,[55][56][57][58]. Many suggest low-carbon pathways using the avoidshift-improve (ASI) framework [59][60][61].…”
Section: Assessment Of Transport Sector Emissionsmentioning
confidence: 99%
“…Recently, governments have promoted BEVs by designing investment programs, legislation pieces and taxation policies [1][2][3][4][5][6][7][8], while manufacturers have innovated battery technology to improve performance and also reduce the range anxiety that relates to the poor adoption of BEVs [9][10][11][12][13]. The design of programs and policies alongside the innovation in battery technology are expected to jolt the system and stimulate a future rapid BEV growth, as reflected in demand assessments predicting reasonable market shares by 2020 [1,14,15] and conspicuous market shares by 2030-2050 [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%